Read my mind : young children, poetry, and learning - Sedgwick, Fred (Routledge, 1997)
This book aims to help all those involved with children and their learning through poem-writing. The book begins with an introduction outling the importance of poetry. It discusses poetry in terms of children's learning and the imagination.